Effect of serotonin depletion on vibrissa-related patterns of thalamic afferents in the rat's somatosensory cortex - Bennett-Clarke, CA (J Neurosci, 1994)
To investigate the role of 5-HT in the development of the somatosensory cortex, this amine was depleted in newborn (P-0) rats with a single subcutaneous injection of the toxin 5,7-dihydroxytryptamine (5,7-DHT) and thalamocortical organization was assayed by application of the carbocyanine dye Di-I to the thalamocortical radiations or ventrobasal thalamus, or by staining cortical sections for AChE or cytochrome oxidase (CO). High-performance liquid chromatographic analysis of cortices from animals killed on P-6 or P > 60 demonstrated that 5,7-DHT treatment resulted in 85.04 +/- 12.6% and 72.5 +/- 1.5% reductions in cortical 5-HT, respectively. Alternate cortices from the brains of animals killed on P-6 processed for 5-HT immunoreactivity demonstrated a complete absence of the vibrissa-related pattern of immunoreactivity and only a small number of coarse immunoreactive axons. The 85% depletion of 5-HT did not alter the somatotopic organization of thalamocortical afferents in animals killed on P-6 or P > 60, but it did cause 30.5 +/- 7.3% and 19.1 +/- 3.7% reductions in the cross- sectional areas of the patches of thalamocortical afferents corresponding to the long mystacial vibrissae (p < 0.05). These reductions were not associated with significant reductions in either brain or cortical weight or with decreases in the dimensions of the thalamic representation of the vibrissa follicles. These results indicate that 5-HT plays a significant role in the development of the thalamic innervation of the primary somatosensory cortex.